Pengembangan Media Pembelajaran E-Learning Dengan Model Pembelajaran Flipped Classroom Berbasis Edmodo Pada Mata Pelajaran Informatika - Dedi Rahman; P Wayan Arta Suyasa; Dessy Seri Wahyuni (Universitas Pendidikan Ganesha, 2021)
The purpose of this study were (1) Produced a design and implemented the development of e-learning learning media with Edmodo-based Flipped Classroom model in Informatics subject of class VII in SMP Negeri 2 Mengwi, (2) Determined the subject teacher and students’ responses towards the development of e-learning learning media with Edmodo-based Flipped Classroom model in Informatics subject of class VII in SMP Negeri 2 Mengwi. The study was a Research and Development (R&D) research with ADDIE development model. This study involved students from VII A class and teacher of Informatics subject in SMP Negeri 2 Mengwi. The method of data collection was questionnaire. The result of the study showed that (1) The design and the implemented e-learning media were success implemented based on validity test from content experts, design experts, and learning media experts with Aiken's V coefficient average score 0,89 and very valid, (2) The teacher and students’ responses showed the average score were 40 for the teacher and 61,8 for the students, meaning that it was included in very positive category with very practical criteria.